Expression of the transcriptional activator LAC9 (KlGAL4) in Kluyveromyces lactis is controlled by autoregulation. - Zachariae, W (1993)
The concentration of the transcriptional activator LAC9 (KlGAL4) of Kluyveromyces lactis is moderately regulated by the carbon source as is the case for GAL4, its homolog in Saccharomyces cerevisiae. Expression of the LAC9 gene is induced about twofold in galactose. This induction is due to autoregulation. The LAC9 gene product binds to a low-affinity binding site in the LAC9 promoter and moderately activates transcription in response to galactose above a basal level. As for the LAC9-controlled metabolic genes, induction of LAC9 is inhibited in the presence of glucose. This inhibition of induction is a prerequisite for glucose repression of the lactose-galactose metabolic pathway. On the other hand, induced LAC9 levels are required for optimal growth on galactose, since mutating the LAC9 binding site in the LAC9 promoter resulted in poor growth and reduced expression of LAC9-controlled genes. Thus, in addition to the GAL80-dependent regulation by protein-protein interaction, the regulation of LAC9 gene expression is an important parameter in determining carbon source control of the LAC-GAL regulon. Although the mode of control is different, the pattern of LAC9 gene regulation resembles that of the S. cerevisiae GAL4 gene, being lower in glucose and glucose-galactose than in galactose.